Emotional intelligence and its relationship to mental health - Al-Qaisi, Jihan Abid Haddad (Al-Adab Journal, 2019)
Many educators and researchers in the field of educational psychology believe that we teach students to achieve a main goal: to provide them with knowledge, theories and facts that constitute a necessary knowledge structure for them, or at best to create a scientific mentality.The high level of their academic performance to reach the levels set by the educational authorities. Most educators and researchers have long believed that mental ability is a key determinant of success in the general academic performance of the learner, as indicated by IQ, but after the emergence of new theoretical perceptions since the end of the last century (such as Gardner's theory of Multiple Intelligences and Emotional Intelligence Theories of Meyer, Salovi and Gulman are no longer the only predictors of success in school - and in life in general - or predictors of this success. Mental health is a consistent organization between the factors of mental composition and the emotional factors of the student because they are negatively or positively affected N Because of human influences plaguing the mind and conscience as it turns these influences student psychological health towards both or Allaswae which draws the limits and the nature of his life and future, and most of these effects impact life pressures living crises plaguing the mind student and controls. The current search aims to identify the conscienceFirst: To measure the level of emotional intelligence among the students of the sample as a whole.Second: To measure the level of mental health among students in theThird: To measure the level of mental health among middle school students according to the following variables . Gender (males and females). Academic specialization Fourth: To reveal the relationship between the variables of emotional intelligence and mental health among students in the research sample.In order to achieve the objectives of the current research, the sample was randomized and in an equal manner of (100) male and female students in the preparatory stage of the second Karkh Directorate according to the sex variables (males and females) and the (literary and scientific) In order to measure the level of emotional intelligence among the students, the researcher adopted the Othman and Rizk scale (2001). The number of paragraphs (58) divided it into five areas (emotion management, empathy, emotions, emotional knowledge, social communication) The paragraphs of the scale on a group of experts and specialists in psychology and psychological measurement and through their views was deleted (5) paragraphs and remained (53) paragraphs valid and also extracted the self-honesty of the scale and the total score of the scale according to this honesty (0.93) The other method used by the researcher to extract the stability of the emotional intelligence scale is the coefficient of Alpha Kronbach, where the stability (0.85) It is The mental health measure was prepared by the researcher. The scale consists of 24 parts divided into five areas (health, physical, spiritual, social, mental). The necessary cycometric characteristics of virtual honesty and indicators of the validity of construction (5) paragraphs were excluded because they are less than the required level of significance and the addition of one paragraph of the scale, if the standard became the final image (20) paragraph distributor (5) areas (Recessive and retest), with a consistency coefficient of( 0.80) (0.88), respectivelyThe researcher reached the following results:The members of the elite of the preparatory students enjoy intelligence and conscience according to the results of the researcher..The members of the preparatory students enjoy psychological health according to the results of the researcher..There are no statistically significant differences in the sex factor between males and females according to the mental health variable. There are also no statistically significant differences in mental health according to variablespecialization). )..There is a positive correlation between emotional intelligence and mental health, the more emotional intelligence increased mental health and vice versa ..In the light of the findings of the researcher, I made a number of conclusions, recommendations and suggestions mentioned in chapter IV.